PENGEMBANGAN TRADISI KEILMUAN PADA MASYARAKAT ISLAM KONTEMPORER - AFANDI, MUHAMAD (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2015)
In the era contemporary development of the science is evolving very fast. Each of the discipline of the science developed scientific and create a various of inventions. This should be accepted. facing and offset by the increase in scientific knowledge are adequate so that Muslims do not failed experience by an increasingly forward without forget about eliminating Islamic identity. Muslims need to combine intellectual mindset. deductive-inductive and daring use of academic-philosophical mindset to unlock insight within a Muslim that Islam was a religion that invites people to reach for the happiness afterlife of the world. materially-spiritual and body-spiritual. because intrinsically. human was created to live in the world. Insightful thinking as it forms the scientific tradition of the Muslim integrality - interconnectivity. Pluralities and relativities of Islamic should be realized within the Muslim Ummah. This is will bring the implications against the diversity of Muslims in the future. toward on openness and dialogist. Thus. Muslims can answer the challenge of the times. and give the solving toward a various problems. not only faced by the Muslims themselves. but also in general humanity